Virtual Reality Job Interview Training for Adults Receiving Prison-Based Employment Services: A Randomized Controlled Feasibility and Initial Effectiveness Trial - Smith, Matthew J.; Parham, Brittani; Mitchell, Jamie; Blajeski, Shannon; Harrington, Meghan; Ross, Brittany; Johnson, Jeffery; Brydon, Daphne M.; Johnson, Jennifer E.; Cuddeback, Gary S.; Smith, Justin D.; Bell, Morris D.; et al. (Criminal justice and behavior, 2023)
Returning citizens struggle to obtain employment after release from prison and navigating job interviews is a critical barrier they encounter. Implementing evidence-based interview training is a major gap in prison-based vocational services. We conducted a randomized controlled trial (RCT) to evaluate the feasibility and initial effectiveness of Virtual Reality Job Interview Training (VR-JIT) within two prisons. Forty-four male returning citizens were randomized to receive service-as-usual (SAU) with VR-JIT (SAU + VR-JIT, n = 28) or SAU (n = 16). Participants reported VR-JIT was highly acceptable and usable. SAU + VR-JIT, compared with SAU, had significant improvements (with large effect sizes) in interview skills, interview training motivation, and interview anxiety (all p < .05; η p 2 > .15), and greater employment by 6-month follow-up (odds ratio [OR] = 7.4, p = .045). VR-JIT can potentially help fill a major gap in prison-based services. Future research is needed to validate VR-JIT effectiveness and evaluate VR-JIT implementation strategies within prisons.